2015
DOI: 10.1002/crat.201400304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH value on the growth morphology of KH2PO4 crystal grown in defined crystallographic direction

Abstract: KH2PO4 single crystals were grown in aqueous solution at different pH values by using “point seeds” with a defined crystallographic direction at 59 degree to the Z axis. Atomic Force Microscope (AFM) was applied to observe the surface morphology of (100) face. It was found that at the same supersaturation, the larger steps appeared at the lower pH value before appearance of 2D nucleus. We found that 2D nucleus was occurred at σ ≤ 0.04 when pH value is <2.8. The occurrence of 2D nucleus was caused by the decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the classic work on the crystals growth, BCF showed that the critical radius was related to the supersaturation σ by [14] r c = wα/kTσ (12) By combining the previous Rashkovich's studies [24], the critical radius for σ = 0.09 could be calculated to be about 4.61 nm. The value was far less than the radius of protuberance measured in Figure 7a.…”
Section: Appearance Of Pits At High Supersaturationmentioning
confidence: 91%
“…In the classic work on the crystals growth, BCF showed that the critical radius was related to the supersaturation σ by [14] r c = wα/kTσ (12) By combining the previous Rashkovich's studies [24], the critical radius for σ = 0.09 could be calculated to be about 4.61 nm. The value was far less than the radius of protuberance measured in Figure 7a.…”
Section: Appearance Of Pits At High Supersaturationmentioning
confidence: 91%
“…Enigmatically KDP crystal finds exclusive application in classified path breaking facilities and is most capable material for fabricating elements utilized in lasers, optical switching, optical gates, frequency multipliers, harmonic generation, optical parametric oscillators, optoelectronics and photonic devices . Due to such high technological impetus many research groups have focused their attentiveness to grow fine quality KDP crystal either by employing different growth techniques or by optimizing growth parameters or by doping a selected quantity of impurity (organic/inorganic/semiorganic) . Our research group has been constantly striving to unveil the doping effect of carboxylic acid (viz.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the adjustment of solution acidity may change the growth rate of 98% DKDP crystal greatly. The lower acidity will restrict the growth rate of prismatic faces, and this property has been expounded in other research studies [33,34]. Therefore, it is still necessary to choose a proper pD value solution for crystal growth, which can both shorten the growth period and reduce NLA.…”
Section: Resultsmentioning
confidence: 99%